Pengaruh Green Accounting, Struktur Modal, dan Pertumbuhan Penjualan Terhadap Kinerja Keuangan - Pertiwi, Mentari Nur; Ditya Wardana (Universitas Sains dan Teknologi Komputer, 2025)
The purpose of this research is to analyze the relationship between financial performance, green accounting, and capital structure. The research covered 72 food and drink producers that were listed on the BEI in the years 2019–2022. Twenty businesses were chosen through a purposeful sampling process. Multiple linear regression analysis of secondary data is performed in SPSS 26. According to research, green accounting helps companies improve their financial performance by financing large environmental costs. Financial performance is impacted by capital structure, which in turn increases profits and debt levels. Revenue growth, however, has no bearing on bottom-line results